Effects of Left Renal Vein Ligation During Open Abdominal Aortic Aneurysm Repair on Renal Function. (December 2020) - Pandirajan, Kamashi; Katsogridakis, Emmanuel; Sidloff, David; Sayers, Robert D.; Bown, Matthew J.; Saratzis, Athanasios
Abstract : Objective: Left renal vein (LRV) ligation is performed during open abdominal aortic aneurysm (AAA) repair to facilitate proximal anastomosis. Its impact on short, medium, and long term renal function has not been investigated in detail using appropriately validated endpoints. Methods: This was a nested case control study using data from a prospectively maintained AAA institutional dataset (tertiary centre). A total of 76 patients who underwent elective open AAA repair and had LRV ligation (1 January 2012 to 1 January 2018) were individually case matched based on age (within two years), sex, estimated glomerular filtration rate (eGFR), American Society of Anesthesiologist (ASA) score, chronic kidney disease (CKD) stage, and history of diabetes with 76 patients who had open AAA repair without LRV ligation. Renal outcomes were compared between groups, including proportion of patients developing acute kidney injury (AKI) using the Kidney Disease Improving Global Outcomes (KDIGO) criteria, proportion developing major adverse kidney events (MAKE90) at 90 days (comprising mortality and/or decrease in eGFR >25%), and absolute decrease in eGFR at latest follow up. Results: A higher proportion of patients developed AKI and MAKE90 in the LRV ligation group (AKI: 11 patients [14.8%] vs. 2 [2.6%], p  = .009; MAKE90: 6 [7.9%] vs. 1 [1.3%] p  = .053, in the LRV ligation and the non-LRV ligation groups, respectively) – even though the difference in the MAKE90 endpoint was not statistically significant. Changes in eGFR were not statistically different in the LRV ligation group at 90 days (4.0 ± 1.1 mL/min/1.73 m 2 vs. 4.4 ± 2.1, p  = .64) or by the time of latest follow up (median: 28 months; 3.7 ± 1.6 vs. 2.6 ± 2.0, p  = .55). Conclusion: Ligation of the LRV is associated with increased levels of AKI and renal deterioration in the early post-operative phase using validated reporting criteria; however, long term renal function does not seem to be affected.